INTERPRETASI STRUKTUR BAWAH PERMUKAAN GUNUNG MURIA MENGGUNAKAN ANALISA DATA GRAVITASI - Balulu, Nasrun (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2011)
A geophysical survey using gravity method was carried out in Muria volcano. This research aimed to interpret the subsurface geology condition of the research area based on gravity data analysis. Research area is (47,6 x 45) km2 with 222 observation points. Gravitymeter LaCoste Romberg type G-1118 MVR was used to measure the gravity field, and differential method of Global Positioning System (GPS) was used to measure the position and elevation.Data processing was performed to gain complete Bouguer anomaly of both residual and regional. Bouguer density using graphical method resulted to the value of 2.67 gr/cm3. Transformation to a horizontal plane was performed obtain by using equivalent mass method with horizontal level’s height of 1602 meters beyond the spheroid reference and equivalent The separation of regional anomaly and residual anomaly was generated through upward continuation method and resulted to regional anomaly in the height of 15000 meters up the spheroid reference. The residual anomaly acquired by subtract the regional anomaly toward the complete Bouguer anomaly in a horizontal plane.The subsurface modelling of Muria volcano and its surrounding was acquired from Grav2DC for Windows. The result shows that Muria volcano and its surrounding was regionally controlled by rock resulted from volcanic processes as lava (density 2,91 gr/cm3). This volcanic rock due to the gravity collapse performed a caldera filled by andesit (density 2,58 gr/cm3). Another rock which is deposited in Muria volcano are tuff from Muria Tuff (density 2,4 gr/cm3), tuff sandstone from Patiayam formation (density 2,5 gr/cm3), limestone from Bulu formation (density 2,7 gr/cm3), and limestone from Ngrayong formation (density 2,8 gr/cm3).Keywords:Bouguer anomaly, Regional anomaly, Residual anomaly, Modeling, Subsurface stracture.